Digital Innovation: Teaching Materials with Clean Air for Health Theme for Fifth Grade Elementary School - Rati, Ni Wayan; Agustiana, I Gusti Ayu Tri; Anggreni, Ni Made Dyan (Journal of Education Technology, 2024)
Teaching materials are supporting factors that must exist in learning. One solution that teachers can do to support independent learning activities by students is to provide digital teaching materials that can be used by students anytime and anywhere. This research is development research, which aims to develop digital teaching materials for fifth grade elementary school students. Development research is using the 4D development model (Define, Design, Develop, Disseminate). The data collection method used in this study is a questionnaire or questionnaire method. Product trials were carried out through the assessment of experts and practitioners (3 experts and 2 practitioners) to determine the validity of the teaching materials developed. In addition to testing the validity, trials were also carried out in small groups to find out the practicality of the teaching materials being developed. Data analysis used two analytical techniques (combination method), namely descriptive and inferential data analysis techniques. The results showed that the teaching materials developed were in the category of very high validity and based on the responses from users, both teachers and students regarding practicality, that the teaching materials developed were in the very practical category.